Tensions of a Community Center: Analysis based on Community Psychology in Chile - Carrasco-Aguilar, Claudia; Cerda-Gonzalez, Gustavo; Baltar-de Andrade, María Julia; Zamora-Astudillo, Cristian; Castillo-Muñoz, Álvaro (Revista de Psicología, 2016)
Through a study case based on observations, interviews and a focus group, this article seeks to describe the tensions that arise in a collective organization, which becomes independent of a non-government organization in an emerging community center in the region of Valparaiso, Chile (fifth region). This tensions are related to the subjectivity of the community psychologist which is constructed in said context. The results show an initial disciplinary tension, which refers to the role of the psychology in the community center and a second political tension, which analyzes the social function of the community center and the volunteer work as mechanism for that function.